2022
DOI: 10.2147/ppa.s335363
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Diabetes Self-Management Among Patients with Type 2 Diabetes: A Chinese Cross-Sectional Survey Based on Self-Determination Theory and Social Support Theory

Abstract: Purpose Self-management behavior (SMB) plays a significant role in glycemic control. This study aimed to explore the factors related to SMB among patients with type 2 diabetes and how these factors interacted with each other. Patients and Methods Patients diagnosed with type 2 diabetes were recruited from 18 community healthcare stations (CHSs) from six community healthcare centers (CHCs) in Beijing, China from April to May in 2017. Motivation, competence, autonomy supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The study showed that health beliefs were significantly negatively associated with HbA1c levels and could be used as a negative predictor of HbA1c control, health beliefs may contribute to poor glycaemic control in patients through differences in perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action. 35 Positive health beliefs help to improve the management of patients' blood sugar and have a significant impact on health behavior, 36 consistent with the findings of randomised controlled trials. 37,38 Further analysis showed that except for perceived severity, the other four dimensions were negatively correlated with glycosylated hemoglobin level.…”
Section: Dovepressmentioning
confidence: 58%
“…The study showed that health beliefs were significantly negatively associated with HbA1c levels and could be used as a negative predictor of HbA1c control, health beliefs may contribute to poor glycaemic control in patients through differences in perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action. 35 Positive health beliefs help to improve the management of patients' blood sugar and have a significant impact on health behavior, 36 consistent with the findings of randomised controlled trials. 37,38 Further analysis showed that except for perceived severity, the other four dimensions were negatively correlated with glycosylated hemoglobin level.…”
Section: Dovepressmentioning
confidence: 58%
“…Although there are a variety of self-monitoring equipment and supplies for blood glucose in China, the price of blood glucose meter and blood glucose test paper is a certain pressure for patients with poor economic affordability, which leads to a low compliance of SMBG in some T2DM patients. From the perspective of objective factors, it is found that the lack of blood glucose meter is one of the obstacles of SMBG in diabetic patients ( 27 ). While patients with blood glucose meters tend to have higher frequency SMBG, because having blood testing equipment can makes it easy for patients to perform SMBG ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the subscale "social relations," items highlighted challenges like others finding diabetes unattractive, restricted relationships due to diabetes, social perceptions. In the "emotional worries" subscale, items indicated feeling upset, worried due to diabetes-related issues [14,15,16,17,18] . The "physical complaints" subscale items pointed to pain, skin problems, fatigue, and dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Vol. 14, Issue 4, October -December, 2023 Researchers and clinicians may extend this work to validate its psychometric properties by collecting data from other provinces of Pakistan or may translate this scale into their specific regional languages as well.…”
Section: Discussionmentioning
confidence: 99%